Iowa RBA, April 24-26, 1995 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1995)
Iowa RBA update for April 24-26, 1995. Highlights of the update include sightings of a Reeve (female Ruff), Fish Crows, Sandhill Crane, and Cinnamon Teal. Also included are handwritten notes for the next week's update with sightings of a Bewick's Wren nest, Pine Warbler and a Peregrine Falcon. Epson - sheet feed/flatbed